Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas